Fibrinolysis in Acute and Chronic Cardiovascular Disease - Kietsiriroje, Noppadol; Ariëns, Robert A.S.; Ajjan, Ramzi A. (Seminars in Thrombosis and Hemostasis, 2021)
The formation of an obstructive thrombus within an artery remains a major cause of mortality and morbidity worldwide. Despite effective inhibition of platelet function by modern antiplatelet therapies, these agents fail to fully eliminate atherothrombotic risk. This may well be related to extensive vascular disease, beyond the protective abilities of the treatment agents used. However, recent evidence suggests that residual vascular risk in those treated with modern antiplatelet therapies is related, at least in part, to impaired fibrin clot lysis. In this review, we attempt to shed more light on the role of hypofibrinolysis in predisposition to arterial vascular events. We provide a brief overview of the coagulation system followed by addressing the role of impaired fibrin clot lysis in acute and chronic vascular conditions, including coronary artery, cerebrovascular, and peripheral vascular disease. We also discuss the role of combined anticoagulant and antiplatelet therapies to reduce the risk of arterial thrombotic events, addressing both efficacy and safety of such an approach. We conclude that impaired fibrin clot lysis appears to contribute to residual thrombosis risk in individuals with arterial disease on antiplatelet therapy, and targeting proteins in the fibrinolytic system represents a viable strategy to improve outcome in this population. Future work is required to refine the antithrombotic approach by modulating pathological abnormalities in the fibrinolytic system and tailoring therapy according to the need of each individual.
Keywords: fibrinolysis; fibrin; lysis time; cardiovascular disease